A drug safety evaluation of mirabegron in the management of overactive bladder. Issue 5 (3rd May 2016) - Robinson, Dudley; Thiagamoorthy, Ganesh; Cardozo, Linda
ABSTRACT: Introduction : Overactive Bladder (OAB) is a clinical syndrome describing the symptom complex of urgency, with or without urgency incontinence and is usually associated with frequency and nocturia. Antimuscarinics are currently the most widely prescribed drugs for OAB although persistence with medication is often limited due to lack of efficacy or intolerable adverse effects. Mirabegron is β3 adrenoreceptor agonist that is the first new drug licensed for the management of overactive bladder (OAB) in over 30 years. Areas Covered : This review provides a comprehensive overview of the mirabegron clinical trials programme, including Phase II, III and IV studies with a particular focus on tolerability and safety. A literature search was performed in Pubmed using the key words 'mirabegron', 'overactive bladder', 'β3 adrenoceptor agonist' and 'detrusor overactivity' with no restriction on dates. Expert Opinion : The extensive clinical trial programme has shown mirabegron to be safe and efficacious in the treatment of OAB symptoms and the evidence would suggest that it offers an effective alternative to antimuscarinic therapy.